KASUS ANALISIS KONTRASTIF BAHASA INDONESIA DAN BAHASA ARAB SERTA IMPLIKASINYA DALAM PENGAJARAN BAHASA (Analisis Deskriptif Metodologis) - Moh Pribadi (Adabiyyāt: Jurnal Bahasa dan Sastra, 2013)
The term "contrastive analysis" (CA) can be defined as how to compare two or more languages in synchronic not diachronic analysis including phonetic elements, morphemic, syntactic, and discourse for the sake of teaching and translation discourse. CA purpose is to look for similarities and differences between two or more languages as the object of study. Benefit from the findings of CA can be used as one of the basic considerations in developing language teaching syllabus and in selecting appropriate translation pattern. This practical method of analysis of language has experienced the ups and downs from time to time which in turn gave birth to two powerful streams (strong version) and weak (weak version). Nevertheless, CA is still needed in the world of foreign language teaching does not turn a blind eye to the weaknesses and strengths. Basically there is no single approach that perfect language, so the use of comprehensive methods are a good choice can therefore complement each other. Implications of CA will give influence to teachers, subject matter, and syllabus. Through this analysis, a language teacher can display methods, materials and cargo with special and specific ways. While, the subject matter may be submitted with varying intensity through the CA of the findings of aspects of equality and difference. Syllabus based CA can determine the design of the learning and acquisition targets with existing time allocation.